A Microfluidic Model with Hydrogel Barriers for the Construction of Shear‐Free Attractive and Repulsive Cue Gradients. Issue 2 (4th December 2018) - Liu, Wenming; Han, Kai; Sun, Meilin; Huang, Zhongchao; Wang, Jinyi
Abstract: Axon guidance is a fundamental process during neural development and regeneration. The combinatorial impacts of guidance cues on neuronal axons remain largely unexplored, owing to the lack of micromanipulation methods to conduct such studies. Herein, a microfluidic platform is reported for simultaneously establishing multi‐biochemical cue gradients to investigate attractive and repulsive response integration of axons. The employment of multidirectional hydrogel barriers permits a facile, stable, and long‐term production of shear‐free single linear and double radial biochemical gradients in the device. On‐chip cultivation of primary cortical neurons is favorably performed with microscale control while preserving their high viability, typical neuronal phenotype, and neurite growth and orientation. The applicability of the established platform in studying the complex integration of netrin‐1 and slit‐2 cue gradients by axons and their corresponding responses is experimentally demonstrated. The results indicate that axon guidance in a complex neural microenvironment is strongly associated with the concentration and guiding duration of biochemical signals, providing composite insight into the guidance mechanism underlying the combinatorial effects of netrin‐1 and slit‐2 on neuronal axons. This platform, which has the capability of multiple biochemical gradient control in time and space, holds great potential for applications in neurobiology, oncology, inflammation, and precision medicine. Abstract : Synchronous on‐chip construction of multiple biochemical cue gradients and its applicability in studying complex integration of attractive and repulsive signals by neuronal axons and their corresponding responses are demonstrated. This microfluidic multigradient approach may pave the way to perform on‐chip establishment and micromanipulation of biomimetic tissue microenvironment for research on neurodevelopment, tissue repair, and tumor metastasis.